Irisin participates in the beneficial effects of exercise in preventing gestational diabetes mellitus in overweight and obese pregnant women and a mouse model - Wang, Chen; Zhang, Xiaoming; Liu, Minghui; Qin, Shengtang; He, Chengrong; Liu, Yingnan; Huai, Jing; Zhang, Qidi; Wei, Yumei; Yang, Huixia (Frontiers in Nutrition, 2023)
Objective: We aimed to explore whether irisin participates in the beneficial effects of exercise in preventing GDM in overweight and obese pregnant women. Study design: Sixty overweight and obese pregnant women each in the exercise and control groups were randomly selected from our previous randomized controlled trial. Eighteen obese model mice were generated and divided into exercise and control groups in which body weight, abdominal circumference, rectal temperature, glucose tolerance test and insulin tolerance test were recorded. The plasma irisin level, the expression of PGC-1α/FNDC5 and brown (UCP1) and beige adipose (CD137, TMEM26, and TBX-1) marker genes were detected in muscle and adipose tissue. Results: In the human study, women in the exercise group had a significantly higher irisin level and lower insulin resistance level than those in the control group. Enhanced expression of beige adipose tissue marker genes (CD137, TMEM26, and TBX-1) in omental adipose tissue and the CD137 gene in subcutaneous adipose tissue were found in the exercise group compared to the control group. In a mouse model, body weight and abdominal circumference were decreased, while glucose homeostasis and insulin sensitivity were significantly improved, and rectal temperature was elevated after exercise intervention. A significantly higher level of irisin was revealed in the exercise group after undergoing exercise treatment. The expression of the beige adipose marker genes CD137 and TBX-1 was significantly higher in the exercise group than in the control group in interscapular adipose tissue. Conclusion: Our observations show that regular exercise during pregnancy can increase irisin levels, promote white fat beiging/browning, improve glucose homeostasis and enhance body energy expenditure, which may be one of the mechanisms by which exercise prevents GDM.